Mothers’ Depression and Stress, Severity of Autism among Children and Family Income - Pegah Athari (Universidad de San Buenaventura, 2013)
This study was conducted to investigate the relationship between mothers’ depression and stress compared with severity of autism in children and the effect of family income on the relationship between these two latter variables. Levels of depression and stress among mothers (n=250) were measured based on Depression Anxiety and Stress Scale of 42 items (DASS¬-42). The severity of autism among children was assessed by Autism Behavior Checklist (ABC) according to children’s teachers reports (n=250). Family income was recorded based on mothers’ report and it was investigated as a mediator for the relationship between mothers’ depression-stress and severity of autism among children. Results showed that different incomes of mothers have significant effect on the level of depression and stress among mothers and the severity of autism; besides, results indicated that severity of autism in children changes with family income and mothers’ depression and stress-severity.